2016
DOI: 10.1177/2049463716657364
|View full text |Cite
|
Sign up to set email alerts
|

A service improvement project to review prescribing information provided by general practitioners for new referrals to a UK National Health Service hospital pain clinic: potential implications of CYP2D6 enzyme inhibition

Abstract: Introduction: Chronic pain is often managed using co-prescription of analgesics and adjuvants, with concomitant medication prescribed for comorbidities. Patients may have suboptimal response to some analgesics or be at risk of drug interactions or adverse drug reactions (ADRs) due to polypharmacy affecting CYP2D6 enzyme activity. The aim of the service improvement project was to determine the proportion of patients referred to a specialist pain service in the UK National Health Service (NHS) by general practit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Phenoconversion is likely common, as data indicate approximately 20–30% of patients treated for pain are prescribed a CYP2D6 inhibitor. 18,19…”
Section: Introductionmentioning
confidence: 99%
“…Phenoconversion is likely common, as data indicate approximately 20–30% of patients treated for pain are prescribed a CYP2D6 inhibitor. 18,19…”
Section: Introductionmentioning
confidence: 99%
“…At enrolment, 59% of our sample had been prescribed analgesics dependent on CYP2D6 activity such as co-codamol and tramadol, a similar percentage to a recent service improvement project that reviewed prescribing information provided by general practitioners (GP) for new referrals to a UK National Health Service hospital pain clinic [37]. Prescribers are advised to review medication within 2–4 weeks after titration to identify patients that are unlikely to respond [51], although in our sample 70% of participants reported that they had previously failed to respond to one or more CYP2D6 analgesics despite still consuming such medication.…”
Section: Discussionmentioning
confidence: 99%
“…However, CYP2D6 screening is not part of current clinical practice. We previously reported that 19.9% of patients referred by primary care physicians to a secondary care specialist pain management clinic were at risk of drug interactions associated with co-prescription of analgesic prodrugs reliant on CYP2D6 and CYP2D6 inhibitors [37]. A method of inferring phenotype without the need for genotyping is needed at the point of care.…”
Section: Introductionmentioning
confidence: 99%
“…This issue of the British Journal of Pain ( BJP ) includes a service evaluation by Johnson et al 1 which identified that 8% of referral letters did not even contain information about current analgesics and 20% did not contain information about other medicines. Around a one-fifth of patients were at risk of suboptimal analgesic response or developing side effects due to interaction with other medicines metabolised by the CYP450 2D6 isoenzyme.…”
mentioning
confidence: 99%